(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Social realism is a broad term that has often been used in literature, paintings and other formsof arts. It does not belong to any particular age, nor can it be assigned a particular place in the history.Time and again artists have used it in the art form to express the condition of working class or the realpicture of the society. Bhattacharya’s short stories are inextricably interwoven with the theme of socialrealism. The present article highlights the use of this technique which Bhabani Bhattacharya has used indelineation of characters in his short stories.